Assessment of Knowledge and Perception of UG, Interns & PG medical students towards Radiation Protection Protocols: A Survey Study - Chirayath, Bijoy; Channe, Pallavi P; Hamid, Nida; Bhanawat, Nilesh; Gulia, Sunil Kumar (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Though, radiography has made the diagnosis of diseases easier and less time consuming, the hazards of radiation to humans cannot be ignored. It is of vital importance that radiation protection protocols are adhered to for the safety of the patient, the environment as well as for self-safety. Objective: To assess the knowledge and perception of undergraduate (UG), Interns & postgraduate (PG) medical students towards Radiation Protection Protocols. Material & Methods: A cross-sectional questionnaire survey was conducted on 182 UG, intern and PG medical students to estimate their knowledge and perception towards Radiation Protection Protocols. A survey questionnaire was created using Google forms and links to the survey were sent to the study participants via email and social media platforms. Results: 68.97% of UG medical students, 73.61% of medical interns and 90.38% of PG medical students were aware of the ALARA principle. Only 34.48% of UG medical students, 41.67% of medical interns and 73.08% of PG medical students were familiar with NCRP and ICRP Recommendations. Only 51.72% of UG medical students, 66.67% of medical interns and 69.23% of PG medical students reported that they provided thyroid collars to patients during radiation exposure. Conclusion: Postgraduate medical students had the highest knowledge and perception towards Radiation Protection Protocols. A large number of UG, intern and PG medical students did not adhere to safe radiological practices.